EFEKTIFITAS PELAKSANAAN UPAYA PAKSA PUTUSAN PENGADILAN TATA USAHA NEGARA YANG TELAH BERKEKUATAN HUKUM TETAP - Delfina Gusman (Masalah-Masalah Hukum, 2010)
The existence of Administration Justice (PTUN) can guarantee the assurance of law was produced by illegal conduct under goverment, in act, it is still far from the society's expectation away. It was caused by running it is infective especially the implentation of force effort the justice verdict over the Administration Law that has been established permanently. This inefeciency was caused by some reasoning both judical reason and non judical reason.This research was performed by using judicial-sociological approach through interviewing and researching relevan literature. The data that has been collected and then to be analized judicial-qualitative away in order to make it come true for supporting the justification them judicial-descriptivelly.The result of this research showed that the force effort to the verdict of justice over the Administration Law that has permanenly been establisihed is imposible to be performed efectively considering the regulation of technical guide which regulated the concern. however, in fact the effort force is possible to do efectively if the justice want to refer it to Jurisprudency and Term of Reference stated on Book II and Justice Administration. In other side, in facing the void the regulation of implementation the effort force to the verdict of Administartion Law that has permanently established in administration justice Padang has been conductud to be ininfective the regulation of effort force as stated on Article 116 statement (4) and (5)Kata Kunci : upaya paksa, efektifitas, pembaharuan